(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This study presents indicators of growth and development of Limousin bull calves in the conditions of Karakalpakstan. It highlights the differences in live weight, absolute growth, and daily growth under various technological conditions in relation to their age dynamics. Conclusions are drawn based on these findings.